Potensi Tepung Ubi Jalar Ungu (Ipomoea batatas l.), Tepung Tempe dan Tepung Udang Rebon Dalam Pembuatan Kukis - Sipayung, Ervissa N; Herawati, Netti; ', Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this research was to acquire best cookies which has high nutrition content from purple sweet potato flour and combination of tempe flour with small shrimp flour and agree with quality standard of cookies (SNI 01-2973-1992) that is maximum 5% of moisture content, maximum 2% of ash content and minimum 6% of protein content. This research used Complete Randomized Design (CRD) with four treatments and four replications. The treatments were K1 (tempe flour 95,24%, small shrimp flour 4,76%), K2 (tempe flour 71,43%, small shrimp flour 28,57%), K3 (tempe flour 47,62%, small shrimp flour 52,38%) and K4 (tempe flour 23,81%, small shrimp flour 76,19). Data were analized using ANOVA and DNMRT the level 5%. The result show that the using of tempe flour and small shrimp flour different in each treatments gave the significant effect to the moisture content, ash content, protein content and calcium content. The best cookies in this research is was K2. Keywords : Cookies, purple sweet potato, tempe flour and small shrimp flour